2015
DOI: 10.1093/jxb/erv527
|View full text |Cite
|
Sign up to set email alerts
|

ZmbZIP91 regulates expression of starch synthesis-related genes by binding to ACTCAT elements in their promoters

Abstract: Starch synthesis is a key process that influences crop yield and quality, though little is known about the regulation of this complex metabolic pathway. Here, we present the identification of ZmbZIP91 as a candidate regulator of starch synthesis via co-expression analysis in maize (Zea mays L.). ZmbZIP91 was strongly associated with the expression of starch synthesis genes. Reverse tanscription-PCR (RT-PCR) and RNA in situ hybridization indicated that ZmbZIP91 is highly expressed in maize endosperm, with less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 62 publications
1
81
0
Order By: Relevance
“…The RSR1 transcription factor belongs to the AP2 group of the AP2/EREBP family, which is characterized by an AP2 domain [20]. AP2/EREBP can recognize the GCAC(A/G)N(A/T)TCCC(A/G)ANG(C/T), DRE, GCC, JERE, CAACA, ACGT, and ACTCAT boxes in the promoters of target genes [38,42,43,44,45,46]. These boxes have been identified in the promoters of some upregulated starch synthesis-related enzyme genes in grains of BSMV-TaRSR1-infected wheat spikes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RSR1 transcription factor belongs to the AP2 group of the AP2/EREBP family, which is characterized by an AP2 domain [20]. AP2/EREBP can recognize the GCAC(A/G)N(A/T)TCCC(A/G)ANG(C/T), DRE, GCC, JERE, CAACA, ACGT, and ACTCAT boxes in the promoters of target genes [38,42,43,44,45,46]. These boxes have been identified in the promoters of some upregulated starch synthesis-related enzyme genes in grains of BSMV-TaRSR1-infected wheat spikes.…”
Section: Resultsmentioning
confidence: 99%
“…These boxes have been identified in the promoters of some upregulated starch synthesis-related enzyme genes in grains of BSMV-TaRSR1-infected wheat spikes. For example, ACGT and ACTCAT boxes were found in the promoters of GBSSI and BEI genes of rice [38,45], and AGPS1 , SSI , SSIIIa , and ISA1 genes of maize, respectively [46]. Therefore, TaRSR1 may directly and negatively regulate the expression of some starch synthesis-related enzyme genes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, thus far there have been only a few reports regarding transcriptional regulation of starch synthesis in cereals. Among them, one barley WRKY transcription factor, SUSIBA2, and three maize transcription factors, ZmNAC36, ZmbZIP91, and ZmEREB156, are thought to regulate the expression of starch-synthetic genes based on transcriptional activation and/or EMSA assays of their promoters (22)(23)(24)(25). Recently, a study in rice showed that OsbZIP58, the closest homologous protein of maize O2, regulates the expression of multiple genes in the starch biosynthetic pathways, and its null mutants cause abnormal seed morphology with decreased amounts of seed starch (26).…”
Section: Significancementioning
confidence: 99%
“…The previous studies also tried to identify TFs regulating synthetic starch genes by coexpression analysis and biochemistry experiments, like the Electrophoretic Mobility Shift Assay (EMSA) and the Dual-Luciferase Reporter (DLR) assay. There have been candidate TFs, including one barley WRKY transcription factor of SUSIBA2, and three maize transcription factors of ZmNAC36, ZmbZIP91, and ZmEREB156, although their regulatory function on starch synthesis remains to be validated (20)(21)(22)(23).…”
mentioning
confidence: 99%